A Web-Based Network Device Inventory and Dynamic QR Code Tracking System: Design, Development, and Evaluation PT. XYZ - Desi Fitriana; Viving Frendiana; Budi Utami (Universitas Multimedia Nusantara, 2025)
PT. XYZ is an internet service provider thatowns various network devices such as routers, switches,and servers. Device management is still performedmanually without digital record-keeping, leading toinefficiencies, particularly in the process of requestingand checking device availability. This study aims todevelop a web-based inventory information system tomanage network devices systematically and efficiently.The system is developed using the Laravel frameworkand PHP programming language, and it is equipped witha dynamic QR Code feature that is automaticallygenerated for each recorded device. The inventoryinformation system website was tested through aContract Acceptance Test involving three user roles:Admin, NOC, and CTO, with an average evaluation scoreof 97.5. In addition, system functionality testing of thesystem was conducted using the black-box testing methodon 75 scenarios, all of which were successfully executed.Security testing results indicated a low security risk level.These overall testing results show that the systemfunctions as intended and capable of meeting user needsoptimally.